PEMANFAATAN MEDIA PEMBELAJARAN UNTUK PENINGKATAN KUALITAS BELAJAR SISWA - M. Miftah (Kwangsan: Jurnal Teknologi Pendidikan, 2014)
ICT (Information and Communication Technology) has tremendous potential to help teachers and students in successful learning. Implementation of ICT-based learning, schools need to do a needs analysis, preparation of the necessary requirements, design models of learning and development. Making it easier for teachers in the use of media in teaching. The importance of instructional media for the education system is to support teaching and learning with the Internet media, computer network, or standalone computer. The success is determined by the ability of learning in a variety of things including: efforts to use the media in a learning activity as resources for learning. The process of utilization of instructional media is a decision taken by the learner (teacher) which is based on the design or the lesson plan. Therefore, the principle of utilization needs to be linked to the needs and characteristics of students. These characteristics with respect to the visual style, auditory, and kinestetika students. By utilizing computer-aided media is expected to increase student interest, so that more teachers on how to optimize the role of the teacher as a facilitator, modiator, motivator, supervisor, and evaluator AbstrakTIK (Teknologi Informasi dan Komunikasi) memiliki potensi yang amat besar untuk membantu guru dan siswa dalam keberhasilan pembelajaran . Implementasi pembelajaran berbasis TIK, sekolah perlu melakukan analisis kebutuhan, penyiapan kebutuhan yang diperlukan, perancangan model pembelajaran serta pengembangannya. Sehingga mempermudah guru dalam memanfaatkan media dalam pembelajaran. Pentingnya media pembelajaran bagi sistem pendidikan adalah untuk mendukung belajar mengajar dengan media Internet, jaringan komputer, maupun komputer standalone. Keberhasilan pembelajaran ditentukan oleh kemampuan dalam berbagai hal diantaranya: upaya memanfaatkan media dalam aktivitas pembelajaran sebagai sumber-sumber untuk belajar. Proses pemanfaatan media pembelajaran merupakan suatu keputusan yang diambil oleh pembelajar (guru) yang didasarkan pada desain atau rancangan pembelajaran. Oleh sebab itu, prinsip pemanfaatan perlu dikaitkan dengan kebutuhan dan karakteristik siswa. Karakteristik ini berkenaan dengan gaya visual, auditorial, dan kinestetika siswa. Dengan memanfaatkan media berbantuan komputer diharapkan dapat meningkatkan minat belajar siswa, sehingga guru lebih pada bagaimana mengoptimalisasikan peran guru sebagai fasilitator, modiator, motivator, supervisor, dan evaluator